DATA PENELITIAN SEBAGAI SUMBER INFORMASI UNTUK MELAYANI PEMUSTAKA DI PERPUSTAKAAN PENELITIAN - Djaenudin, Mohamad (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2020)
This paper explains the importance of research data as a source of information in serving users in research libraries as a result of the open science movement that is spreading around the world. Researchers/scientists are no longer satisfied with the publication of their written work, but primary data produced from research activities also need to be shared through an online repository system. This is in line with the demands of users who are increasingly complex in finding sources of information. Still a small number of research libraries that serve research data make it difficult for users when looking for information on primary/research data. An aspect of the benefits of research data services for research libraries is that they can create opportunities to increase library visibility and expand the role of libraries. The competence of librarians must be prepared to support research data services, given that there is no formal education in this regard. The concept of embedded librarian is possible as a solution through training, internships, and further education related to research data management. The practice of applying the concept of embedded librarians in the context of research places librarians more than just supporting staff, but librarians are placed as partners of researchers in conducting research activities.